New Direction to Evaluate the Economic Impact of Peace for Bilateral Trade among World Economies (The Pakistan Development Review, 2016)
Earlier researchers have been working to relate globalisation, trade or free trade as an instrument for bringing peace and reducing conflict in the world. But this study attempts to open up a new debate that how social unrest in terms of lack of pace in nations leads to failure of economic policing and outcomes. In past, few researchers have tried to show peaceful environment as a generator for economic progress by building theoretical models, but limited empirical analysis has been conducted so far. This brings a novelty in the present study that for the first time a large set of data covering 155 nations has been used to explore the relationship between these two desired variables i.e. trade related variables and peace, in new direction and employing new indicators defining extent of peace in nations. Panel co-integration technique has been applied along with Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) models to know the parametric and non-parametric point estimates of variables. Data has been extracted from Economic Institute of Peace and World Bank for the time period 2008-2014. Results showed that lesser number of attacks are associated with more volume of trade among nations and better relations with neighbouring countries are linked positively with trade performance of nations. Nations involved more into hostility acts like conflicts are unable to maximise the benefits from bilateral trade. JEL Classification: F10, D74, L33, C23. Keywords: Globalisation, Trade, Conflict, Terrorism, Panel Model